Case report: Two siblings with very late onset of holocarboxylase synthase deficiency and a mini-review - Gaschignard, Margaux; Domenach, Louis; Lamireau, Delphine; Guibet, Claire; Roche, Sandrine; Richard, Emmanuel; Redonnet-Vernhet, Isabelle; Mesli, Samir; Lebreton, Louis (Frontiers in Genetics, 2024)
Holocarboxylase synthase (HCS) deficiency is an extremely rare metabolic disorder typically presenting as severe neonatal metabolic acidosis, lethargy, hypotonia, vomiting, and seizures. This report describes two siblings in a family with late-onset forms of HCS deficiency. The younger sister presented at the age of 11 years and manifested as acute metabolic acidosis, which promptly resolved following rehydration and biotin administration. The results of the organic urine profile confirmed multiple carboxylase deficiency, and genetic testing revealed a novel pathogenic variant in the HLCS gene (NM_000411.8) in the homozygous state: c.995A>G; p.(Gln332Arg). No further decompensation was observed for her during the 3-year follow-up period. His older brother was diagnosed at the age of 23 years-old through biochemical tests, without any history of acidotic decompensation. A mini-review of HCS deficiency with late onset (>1 year) or early onset (<1 month) revealed that splice variants are associated with late onset, while both variants p.(Leu216Arg) and p.(Leu237Pro) are associated with early onset. However, the majority of genotypes do not show a clear correlation with the timing of HCS deficiency onset. The most significant point here is the description of extremely late-onset cases of HCS deficiency. This can prompt metabolic investigations and raise suspicion of this rare disease in cases of unexplained metabolic acidosis, even beyond early childhood.